Monitoring COVID-19 Impacts on Firms in Ethiopia, Report No. 6 : Results from a High-Frequency Phone Survey of Firms - Bundervoet, Tom (World Bank, Washington, DC, 2020)
The Coronavirus (COVID-19) pandemic and its negative economic effects create a need for timely data and evidence to help monitor and mitigate the social and economic impacts of the crisis. To monitor the impacts of the Coronavirus (COVID-19) pandemic and related containment measures on formal firms in Ethiopia and inform the policy response, the World Bank, in collaboration with the government, is implementing a high-frequency phone survey of firms (HFPS-F). The HFPS-F interviews a sample of firms in Addis Ababa every three weeks for a total of eight survey rounds, and an additional sample of firms in four other cities in Ethiopia (Adama, Bahir Dar, Hawassa, and Mekelle) for a total of seven rounds. This high-frequency follow-up allows for a better understanding of the effects of and responses to the Coronavirus (COVID-19) pandemic on firm operations, hiring and firing, and expectations of future operations and labor demand in order to better tailor and implement interventions and policy responses and monitor their effects.